1998
DOI: 10.1084/jem.188.11.2175
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell Survival and Maturation Are Regulated by Different Signaling Pathways

Abstract: Although dendritic cell (DC) activation is a critical event for the induction of immune responses, the signaling pathways involved in this process have not been characterized. In this report, we show that DC activation induced by lipopolysaccharide (LPS) can be separated into two distinct processes: first, maturation, leading to upregulation of MHC and costimulatory molecules, and second, rescue from immediate apoptosis after withdrawal of growth factors (survival). Using a DC culture system that allowed us to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
532
1
4

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 634 publications
(581 citation statements)
references
References 37 publications
44
532
1
4
Order By: Relevance
“…TLR, IL-1R, TNF and CD40 receptors lead to activation of downstream signaling cascades such as the NF-jB pathway or the MAP kinase pathways [35]. Thus, it was reported that the ERK1/2 and PI3K pathways were involved in DC survival, whereas the p38 MAPK and the NF-jB pathways were critical for DC maturation [21,36,37]. We have previously shown that JM34 inhibited the PKC-dependent activation of ERK2 in macrophages [18], but this is unlikely to account for the present inhibition of DC maturation.…”
Section: Discussionmentioning
confidence: 99%
“…TLR, IL-1R, TNF and CD40 receptors lead to activation of downstream signaling cascades such as the NF-jB pathway or the MAP kinase pathways [35]. Thus, it was reported that the ERK1/2 and PI3K pathways were involved in DC survival, whereas the p38 MAPK and the NF-jB pathways were critical for DC maturation [21,36,37]. We have previously shown that JM34 inhibited the PKC-dependent activation of ERK2 in macrophages [18], but this is unlikely to account for the present inhibition of DC maturation.…”
Section: Discussionmentioning
confidence: 99%
“…We questioned whether the EPO treatment of BM-DCs activates signal transduction pathways that participate in DC activation (Lindner et al, 2007;Rescigno et al, 1998) 13 and thus focused on the NF-κB, MAPK and AKT pathways. BM-DCs were stimulated with 50 U/ml rHuEPO or with 0.05 µg/ml LPS (positive control) for the indicated time periods and cell lysates were subjected to immunoblot analysis.…”
Section: Epo Leads To Activation Of Multiple Signaling Pathways In DCmentioning
confidence: 99%
“…We showed that EPO-Rstimulation in the BM-DCs activated the MAPK, AKT and NF-κB pathways. These pathways are crucial for the maturation and survival of DCs (Rescigno et al, 1998).…”
mentioning
confidence: 99%
“…Blocking LPS-induced NF-kB activation by the application of TPCK blocks the maturation process of these cells. 28 In addition, pretreatment of DCs with PSI, an irreversible proteasome inhibitor, decreases the antigen-presenting function of these cells. 29 As discussed above, it is clear that NF-kB proteins play a crucial role in DC maturation.…”
Section: Nf-jb and Dcs Differentiation And Maturationmentioning
confidence: 99%